Corporate Governance and Indian Banking Industry - Gupta, Sachindra Kumar; Kumar, Pradeep (Journal of Commerce and Trade, 2009)
The present study aims at examining the governance practice prevailing in the prominent banks of the Indian Banking Industry within the Indian regulatory framework. The most accepted corporate mantra today is that better the C.G. practice of an organization, the better the shareholders and stakeholders value creation. The study aims at assessing the substance and quality of reporting of the corporate governance practice in the annual report. This paper is based on two renowned banks in the banking industry i.e. SBI & ICICI bank, the former being leading public sector bank and the latter being leading private sector bank. The study is based on clause 49 of the Listing Agreement as prescribed by the Securities and Exchange Board of India and Narayan Murthy’s committee report on corporate governance.